Customer Loyalty in the Islamic Banking Industry: Insights from a Case Study of BPRS Puduarta Insani's Marketing Strategy - Amelia Azura; Nurbaiti Nurbaiti; Nur Ahmadi Bi Rahmani (Islamic Economics and Business Faculty of UIN Antasari, 2023)
This research paper examines the role of relationship marketing, sharia compliance, and company image in influencing customer loyalty in the Islamic banking industry, moderated by customer satisfaction. The study focuses on a case study of BPRS Puduarta Insani's marketing strategy in Indonesia. The aim of the study is to provide insights into the factors that contribute to customer loyalty and to identify areas for improvement in the bank's marketing approach. The study uses a quantitative research method, collecting primary data through a Likert scale questionnaire. The data gathered from 99 participants are analyzed using SPSS 21.0, including tests of validity, reliability, classical assumptions, statistical significance, and pathway analysis. The results of the study reveal that variables related to relationship marketing and company image have a positive but insignificant effect on customer loyalty, while variables related to sharia compliance have a positive and statistically significant effect on customer loyalty. The findings suggest that Islamic banks need to prioritize sharia compliance and cultivate a positive image to enhance customer loyalty.Penelitian ini mengkaji peran dari relationship marketing, kepatuhan syariah, dan citra perusahaan dalam mempengaruhi loyalitas nasabah di industri perbankan syariah, yang dimoderatori oleh kepuasan nasabah. Studi ini difokuskan pada studi kasus strategi pemasaran BPRS Puduarta Insani di Indonesia. Tujuan dari penelitian ini adalah untuk memberikan wawasan mengenai faktor-faktor yang berkontribusi terhadap loyalitas nasabah dan mengidentifikasi area yang perlu diperbaiki dalam pendekatan pemasaran bank tersebut. Penelitian ini menggunakan metode penelitian kuantitatif dengan mengumpulkan data primer melalui kuesioner skala Likert. Data yang diperoleh dari 99 responden dianalisis menggunakan SPSS 21.0, termasuk uji validitas, reliabilitas, asumsi klasik, signifikansi statistik, dan analisis jalur. Hasil dari penelitian ini menunjukkan bahwa variabel yang terkait dengan pemasaran hubungan dan citra perusahaan memiliki efek positif namun tidak signifikan terhadap loyalitas nasabah, sementara variabel yang terkait dengan kepatuhan syariah memiliki efek positif dan signifikan secara statistik terhadap loyalitas nasabah. Hal ini mengindikasikan bahwa bank syariah perlu memprioritaskan kepatuhan syariah dan membangun citra positif untuk meningkatkan loyalitas nasabah.